THE STUDY OF SOLO SINGING: PHONATION AND ITS STRUCTURAL COMPONENTS - Shapovalova, Rimma G. (Educological discourse, 2015)
Despite the need for clarification of the essence of phonation and the need for future music teacher of the or etical knowledge about the structure and functioning of the vocal tract and fundamental Bioacoustic patterns that under lie vocal technology, the artic lereveals the structural components of phonation, special attention is paid to the structure and features vocal tract and its importance in learning the solo singing briefly analyzed complementary theory of phonation, conventionally singled in dicators singing phonation, stressed the need to study methods of spectral analysis in vocal pedagogical practice.